2019
DOI: 10.3390/universe5050122
|View full text |Cite
|
Sign up to set email alerts
|

Hadron Spectra Parameters within the Non-Extensive Approach

Abstract: We investigate how the non-extensive approach works in high-energy physics. Transverse momentum (pT ) spectra of several hadrons are fitted by various non-extensive momentum distributions and by the Boltzmann-Gibbs statistics. It is shown that some non-extensive distributions can be transferred one into another. We find explicit hadron mass and center-of-mass energy scaling both in the temperature and in the non-extensive parameter, q, in proton-proton and heavy-ion collisions. We find that the temperature dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The difference of these variations have been studied in details e.g. in [113,114]. It was concluded that all versions of the Tsallis -Pareto fitting functions give a consistent result within the accuracy of the available experimental data.…”
Section: Introduction To the Non-extensive Statistical Frameworkmentioning
confidence: 92%
“…The difference of these variations have been studied in details e.g. in [113,114]. It was concluded that all versions of the Tsallis -Pareto fitting functions give a consistent result within the accuracy of the available experimental data.…”
Section: Introduction To the Non-extensive Statistical Frameworkmentioning
confidence: 92%
“…Power-law functions are used to describe the experimental data for the transverse momentum distribution of particles produced in proton-proton and heavy-ion collisions at the LHC and RHIC energies [1,2,3,4,5,6,7,8]. Now the phenomenological transverse momentum distribution [9,10,11] inspired by the Tsallis statistics [12] has gained much attention and it is successfully used for the description of the experimental data on high-energy proton-proton reactions [13,14,15,16,17,18,19,20,21,22,23,24,25,26] and relativistic heavy-ion collisions [27,28,29,30,31,32]. However, it has some dificulties in relation to the fundamental principles of thermodynamics and statistical mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…As in refs. [56][57][58][59], in this work, we have treated p+p (p+ p) collisions as where a medium was formed, or at least there is some degree of thermalization, enough to have a temperature for the emission source. On the other hand, the temperature parameter of the emission source is a reflection of the average kinetic energy of given particles.…”
Section: Resultsmentioning
confidence: 99%